The role of social media marketing in Ethiopian tourism and hospitality organizations: Applying the unified theory of acceptance and use of technology model - Kassegn Berhanu; Sahil Raj (Cogent Social Sciences)
Being one of the modern marketing technologies, social media marketing is effective to reach the right target market and it is widely utilized by business entities and tourism destinations to promote products and services. Through applying the Unified Theory of Acceptance and Use of Technology model, this research is designed to examine how tourism principal service providers use social media marketing. SPSS version 23 was employed to compute mean, one-way Analysis of variance and multiple regressions. The effective sample size is 176 tourism and hospitality organizations. The findings revealed that performance expectancy, effort expectancy, and facilitating conditions have significant impacts on the use of social media marketing. However, social influence has not a significant effect on the outcome variable. The major implication drawn from the study is that the need to pay due attention to provide appropriate training for tourism and hospitality sectors regarding usefulness and easiness of e-marketing innovations and technologies which helps to devise and implement creative management and marketing strategies that in turn contribute to tourism destinations and organizations to become competitive enough.